Chemical stability and tunable luminescence of Ln(iii)–K(i) coordination polymers featuring a tracery-like architecture1. Issue 61 (4th July 2015) - Li, Qipeng; Yuan, Zeli; Qian, Jinjie; Du, Shaowu
<x xml:space="preserve">Abstract</x> With the help of in situ generation of sulfate anion, three Ln(iii)–K(i) sulfate and oxalate coordination polymers have been synthesized. These compounds display thermal and chemical stability, as well as good temperature and pH sensing ability.